Bridging continents with yam: Australian delegates visit IITA for knowledge exchange - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
A spirit of collaboration, curiosity, and cultural connection defined the recent visit of four Australian delegates to IITA from 7-11 July. The team, led by Professor Yasmina Sultanbawa, Director of Scientific Nutrition and Food Systems, University of Queensland, Australia, enjoyed a weeklong interactive exchange focused on deepening understanding of yam research and exploring innovative strategies to enhance yam production and utilization within Australia, particularly among Indigenous communities. What began as initial conversations between research colleagues across continents became robust interactions across multiple IITA teams, offering the Australian delegation a rich, firsthand exploration of yam breeding, production, and value addition at IITA. Through the training sessions, led by Yam Breeding Experts at IITA, participants gained insight into IITA’s yam breeding strategies, processing techniques, disease and pest management, yam seed systems, pollination, phenotyping, and propagation technologies. Their exploration extended beyond IITA’s campus, including a visit to Bodija Market to observe yam trade dynamics and a tour of NIJI Group’s processing facilities, reinforcing the link between research, industry, and market realities.